(3QSGdI aj GdCSWQdGHs - (3Ydj Hf YjSis
(3ChdgG (B:s
(3Chd eG jMJGL Edjg ai Yde GdCSWQdGH heYQaI dejRGf GdCQJaGY heYQaI CHQI heYQaI GdYfcHhJ Ke eYQaI fWGb GdHQhL s
(3BNQgG (B:s
(3eYQaI WGdY GdSfI hgh Cf JYQa WGdY GdSfI GdeGVjI hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGefIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B845s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3Gdadcs